The formation mechanism of landslides in typical fault zones and protective countermeasures: A case study of the Nanpeng River fault zone - Li, Youjun; Zhang, Hongri; Huang, Liming; Li, Hongming; Wu, Xuexiao (Frontiers in Earth Science, 2023)
Landslides are frequent in the Nanpeng River fault zone in southwest Yunnan. Based on a Zhen Qing Expressway survey, the geological conditions and characteristics of landslides in this area were studied. The conclusions are as follows: 1) the geological background was the internal cause of local highly steep slopes and broken rock masses. The main landslide types in study area are fault-type and accumulation landslides. 2) The formation of fault-type landslides is related to endogenous causes, such as tectonic movements, but they are less easily triggered than accumulation landslides. Accumulation landslides are related to broken rock masses and are sensitive to external factors such as rainfall and artificial unloading. 3) The coordinated control of permanent support engineering, local deformation control, and overall support reinforcement should be considered as preventive measures.